A Paradox: The Declining Achievement of Minimum Education Service Standards vs the Increasing Non-Formal Education Targets - Anugrah, Wahyu; Asmorowati, Sulikah; Irianto, Jusuf (Publik : (Jurnal Ilmu Administrasi), 2025)
This study evaluates the fulfillment of Minimum Service Standards (SPM) in basic education in Lumajang Regency. Using the Human Capital Theory approach, it analyzes how government budget allocation impacts education quality. The findings indicate that despite significant budget allocations, challenges persist in meeting minimum service targets, particularly in equality education. In-depth interviews with Education Office officials reveal several obstacles, including limited resources, inadequate facilities, and low public awareness of equality education. The study highlights that although the Lumajang Regency government has allocated substantial funds for education, disparities remain in service achievements. The budget distribution prioritizes primary and secondary education, while non-formal education, particularly equality education, receives less attention. As a result, the achievement rate for equality education remains significantly lower compared to other educational sectors. To address these issues, this study recommends a more holistic and integrated strategy. Key suggestions include enhancing public awareness campaigns, optimizing non-APBD funding sources such as Corporate Social Responsibility (CSR) initiatives and village funds, and leveraging technology to improve educational accessibility and quality. Additionally, teacher training programs and better infrastructure investments are essential to enhance educational outcomes. A systematic evaluation and monitoring framework, supported by technology and independent institutions, is necessary to track progress and ensure policy effectiveness. By implementing these strategies, the Lumajang Regency government can improve education service standards, reduce disparities, and foster sustainable human resource development.